Exploring English Teacher’s Teaching Strategies to Build Students’ Confidence to Practice Speaking English - Tri Ilma Septiana, Sri Rahayuningsih (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
This study aims to explore English teacher’s teaching strategies to build students’ confidence to practice speaking English. Case study was used as research method with data collection techniques through classroom observation and interviews. The results of this study showed that the three teaching strategies (partner work, modeled talk, and story reenactment) had significant implications for students’ confidence to practice speaking English. This was reflected in various attitudes of students, namely students’ persistence and desire to practice speaking English, a high sense of optimism and learning motivation, students’ open-mindedness to receive positive feedbacks from teacher, mental and physical health state, students’ ability to adapt to subject matter in order to achieve learning objectives, as well as encouragement to become autonomous learners.